The advantage of polyethylene glycol electrolyte solution combined with lactulose in patients with long interval preparation-to-colonoscopy - Hu Yuanchao; Li Xueping; Lin Tao; Niu Jianping; Mi Man (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The main aim of the present study was to assess the efficacy of polyethylene glycol electrolyte (PEG) solution combined with lactulose in bowel preparation to find a new method for colonoscopy preparation to improve the quality of colonoscopy in patients with long interval preparation-to-colonoscopy (P-C). Materials and Methods: A prospective, randomized, endoscopist-blinded and placebo-controlled study was conducted. Three hundred sixty patients who were scheduled for colonoscopy were enrolled in the study. They were randomly divided into the PEG-lactulose group and the PEG-placebo group with 180 patients per arm. Two of the most common methods for estimating the quality of bowel preparation were the use of the Boston Bowel Preparation Scale and the measurement of the Bubble Scale and adenoma detection rate (ADR) as a secondary outcome of observation. Results: The PEG-lactulose group had a significant improvement in the quality of bowel preparation compared with the PEG-placebo group including colon cleanliness in interval P-C at 8 and 9 h (p<0.05) and bubble elimination in interval P-C at 5, 6, 7, 8, and 9 h (p<0.05). Compared with the PEG-placebo group, the ADR (23.3% vs. 15.0%, p<0.05) and the size (≤5 mm) of the adenoma (45.2% vs. 18.5%, p<0.05) increased in the PEG-lactulose group, and there were significant differences between the two groups. Conclusion: PEG solution combined with lactulose can improve the quality of colonoscopy in patients with long interval P-C to allow the patients to select more flexible colonoscopy time. It is worth further popularizing in clinical practice. Cite this article as: Yuanchao H, Xueping L, Tao L, Jianping N, Man M. The advantage of polyethylene glycol electrolyte solution combined with lactulose in patients with long interval preparation-to-colonoscopy. Turk J Gastroenterol 2020; 31(1): 23-9.